THE IMPACT OF LEARNING ASSESSMENT EMERGENCY ON THE EDUCATION QUALITY - Ikhrom, Ikhrom (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2023)
The learning process that switches to the online system requires the enactment of assessment emergencies in various schools. This study aims to determine the assessment process of student learning during Covid-19, the impact of emergency assessment on student conditions during learning, and the implications of emergency assessment on the quality of education. This research method is a mixed method with a phenomenological approach. The instruments used are in the form of questionnaires and interviews. The results of this study show that the emergency assessment was carried out not optimally. The implementation of emergency assessments leads to a decrease in motivation, participation, understanding, and changes in the way students learn. This makes the quality of learning during the Covid-19 period worse. There has been a decline in student motivation, learning achievement, and morals, as well as a cumulation of competency standard (KD) loads at the next level. Abstrak: Proses pembelajaran yang beralih ke sistem online membutuhkan pemberlakuan keadaan darurat penilaian di berbagai sekolah. Penelitian ini bertujuan untuk mengetahui proses penilaian pembelajaran siswa pada masa Covid-19, dampak darurat penilaian terhadap kondisi siswa saat pembelajaran, dan implikasi darurat penilaian terhadap kualitas pendidikan. Metode penelitian ini adalah metode campuran dengan pendekatan fenomenologis. Intrumen yang digunakan berupa kuisioner, dan wawancara. Hasil penelitian ini menunjukkan bahwa penilaian darurat dilakukan secara tidak optimal. Pelaksanaan penilaian darurat menyebabkan penurunan motivasi, partisipasi, pemahaman, dan perubahan cara belajar siswa. Hal tersebut menjadikan kualitas pembelajaran di masa Covid-19 semakin memburuk. Telah terjadi penurunan terhadap motivasi, prestasi belajar siswa, dan akhlak siswa, serta penumpukan beban standar kompetensi (KD) di tingkat berikutnya.